MASALAH-MASALAH SOSIAL DALAM NOVEL TANAH PARA BANDIT KARYA TERE LIYE - Ningsih; La Ode Syukur; La Tike (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
The novel Tanah Para Bandit by Tere Liye serves as the research basis for this study, which focuses on talking about societal issues raised in the book. A novel is a piece of prose fiction that describes the difficult existence of a fictional character or persona. An author's literary works often address societal issues that the author want to make readers aware of. Social difficulties are issues that run counter to societal standards and ideals. What societal issues are raised in Tere Liye's novel Tanah Para Bandit is the wording of the research problem. The purpose of this study is to outline the societal issues raised by Tere Liye's novel Tanah Para Bandit. A qualitative descriptive method was used in this investigation. The research's source material is Tere Liye's novel Tanah Para Bandit, which addresses societal challenges. The data source is Tere Liye's book Tanah Para Bandit, published in 2023 by PT Sabakgrip Nusantara. The methods of analysis and close reading were both used to collect the data for this investigation. The data analysis process employs a literary sociology technique that focuses on the sociology of literary works. The sociological approach to literature focuses on the topic of literary works' contents, objectives, and other components alluded to in the work itself, as well as how these relate to society concerns and the intended message or purpose. Eight different types of social problems were identified as a result of research on the themes of social problems in Tere Liye's novel Tanah Para Bandit. These problems included issues with poverty, violence, family disarray, the younger generation, breaking community norms, population, the environment, and crime.